Prolactin-regulated Pbk is involved in pregnancy-induced β-cell proliferation in mice. Issue 2 (13th December 2021) - Cao, Yan; Feng, Zijie; He, Xin; Zhang, Xuyao; Xing, Bowen; Wu, Yuan; Hojnacki, Taylor; Katona, Bryson W; Ma, Jian; Zhan, Xiaorong; Hua, Xianxin
Abstract : Gestational diabetes mellitus (GDM) is a condition of diabetes with onset or first recognition in pregnancy. Its incidence is increasing, and GDM deleteriously affects both mother and the fetus during and even after pregnancy. Previous studies in mice have shown that during pregnancy, β-cell proliferation increases in the middle and late stages of pregnancy and returns to normal levels after delivery. Hormones, such as prolactin, estradiol, and progesterone as well as protein kinases, play important roles in regulating gestation-mediated β-cell proliferation; however, the regulatory relationship between them is uncertain. We previously found that protein kinase Pbk was crucial for basal proliferation of mouse islet cells. Herein we show that Pbk is upregulated during pregnancy in mice and Pbk kinase activity is required for enhanced β- cell proliferation during pregnancy. Notably, knock-in (KI) of a kinase-inactivating Pbk mutation leads to impaired glucose tolerance and reduction of β-cell proliferation and islet mass in mice during pregnancy. Prolactin upregulates the expression of Pbk, but the upregulation is diminished by knockdown of the prolactin receptor and by the inhibitors of JAK and STAT5, which mediate prolactin receptor signaling, in β-cells. Treatment of β-cells with prolactin increases STAT5 binding to the Pbk locus, as well as the recruitment of RNA polymerase II, resulting in increased Pbk transcription. These results demonstrate that Pbk is upregulated during pregnancy, at least partly by prolactin-induced and STAT5-mediated enhancement of gene transcription, and Pbk is essential for pregnancy-induced β-cell proliferation, increase in islet mass, and maintenance of normal blood glucose during pregnancy in preclinical models. These findings provide new insights into the interplay between hormones and protein kinases that ultimately prevent the development of GDM.